(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2021)
In this work, the space-time variation in macroalgae composition was determined at two sampling sites located in Salango, Manabí province, on the coast of Ecuador. Variations in taxonomic groups, coverage and diversity were recorded over time. The methodology used is sarCE and the marine-coastal ecosystem method manual for establishing environmental impacts. Among the results, Centroceras clavulatum is the species with the largest record in both sampled locations. The largest coverage in the southern station is represented by Chlorophyta (37%), while in the north there was a higher coverage of Rhodophyta (39%). According to the Shannon-Wiener index and maximum diversity value was given in November for the north and south of Salango 2.1 and 2.3 respectively. Temporary variation showed that The Rhodophyta and Chlorophyta groups have changes in the number of individuals between October and November 2019, Diversity rates had high levels in November. The similarity values coincide with species diversity and species richness in November where the highest salinity values were obtained by suggesting that their populations have a number of spatial variations, but do not have parallel dynamics and each group meets different requirements for its population.